Increasing tacrolimus time‐in‐therapeutic range is associated with superior one‐year outcomes in lung transplant recipients. Issue 6 (6th April 2018) - Ensor, Christopher R.; Iasella, Carlo J.; Harrigan, Kate M.; Morrell, Matthew R.; Moore, Cody A.; Shigemura, Norihisa; Zeevi, Adriana; McDyer, John F.; Venkataramanan, Raman
Abstract : Calcineurin inhibitors (CNIs) are the backbone of traditional immunosuppressive regimens for lung transplant recipients (LTR). The CNIs are both narrow therapeutic index drugs with significant interpatient and intrapatient variability that require therapeutic drug monitoring to ensure safety and effectiveness. We hypothesized that tacrolimus time‐in‐therapeutic range (TTR) affects acute and chronic rejection rates in LTRs. This was a single‐center, observational, cross‐sectional study of 292 adult LTRs. Subjects who received tacrolimus posttransplant for the first year were included. TTR was calculated at 1 year using protocol goal ranges (12‐15 mg/mL months 0–6; 10–12 mg/mL for months 7–12). The primary outcome was acute cellular rejection (ACR) burden at 1 year. Chronic lung allograft dysfunction (CLAD), mortality, and infection rate were assessed as secondary outcomes at 1 year. Primary and secondary outcomes were assessed using logistic regression. Increasing TTR by 10% was associated with a significantly lower likelihood of high‐burden ACR at 1 year on univariable (OR 0.46, 95% CI 0.40–0.54, P  < .001) and multivariable (OR 0.64, 95% CI 0.47–0.86, P  = .003) assessment, controlling for age and induction agent. Increasing TTR by 10% was also associated with lower rates of CLAD ( P  < .001) and mortality ( P  < .001) at 1 year. Prospective studies confirming these findings appear warranted. Abstract : In this article, the authors describe the impact of quality immunosuppression management as quantified by time‐in‐therapeutic range (TTR) of tacrolimus and associate changes in TTR with hard outcomes 1 year after lung transplantation.